THE SOCIOCULTURAL IMPACT OF ENGLISH LANGUAGE LEARNING ON IDENTITY CONSTRUCTION AMONG SECOND LANGUAGE LEARNERS IN PAKISTAN AND OTHER FORMER BRITISH COLONIES - Dr Asim Aqeel; Rida Akram; Mahrukh; Zahra Batool (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Language is a fundamental aspect of human identity, mediating our communication with the world and influencing our sense of self. Identity is multifaceted and influenced by various factors, including language and culture. Bilingualism is the norm in many regions of the world, and in Pakistan, multiple languages exist side by side, with English serving as the official language. English has had a significant impact on the identity construction of second language learners in Pakistan and other former British colonies. This chapter aims to explore the relationship between language and identity in a sociocultural context and understand how English language learning and teaching have affected the identity construction of second language learners. The chapter poses several questions, including the definition of identity, the role of sociocultural identity in second language learners, the influence of English as an international language on identity construction, and the current state of identity construction among Pakistani ESL learners. Ultimately, the chapter seeks to provide insight into how to promote positive identity construction through language learning and teaching.